2018
DOI: 10.1088/1361-665x/aade3e
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous realization of large sound insulation and efficient energy harvesting with acoustic metamaterial

Abstract: Acoustic metamaterials, capable of both sound insulation and energy harvesting, composed of Helmholtz resonators and built-in decorated membranes are proposed. It is theoretically and experimentally proved that the proposed metamaterial can obtain two sound insulation bands where the sound energy is also efficiently harvested at the same frequency simultaneously. The peak of the output power can reach up to 244 nW when the incident sound pressure is 1 Pa, which is about 14 times larger than structures composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Acrylic plates were mechanically fastened together using bolts to construct the resonator for sound insulation ( Figure 7a) and energy-harvesting applications. [18] A major advantage of using adhesives is the ability to bond different types of materials together. Other membrane-type AMMs have bonded material layers such as polycarbonate and porous fiberglass wool (Figure 7b), [39] polyurethane and plastic, [26] or latex rubber on aramid fiber sheets.…”
Section: Arrangement and Assembly Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acrylic plates were mechanically fastened together using bolts to construct the resonator for sound insulation ( Figure 7a) and energy-harvesting applications. [18] A major advantage of using adhesives is the ability to bond different types of materials together. Other membrane-type AMMs have bonded material layers such as polycarbonate and porous fiberglass wool (Figure 7b), [39] polyurethane and plastic, [26] or latex rubber on aramid fiber sheets.…”
Section: Arrangement and Assembly Methodsmentioning
confidence: 99%
“…Reproduced with permission. [18] Copyright 2018, IOP Publishing Ltd. b) Layered membrane-type AMM for absorption and broadband insulation. Reproduced with permission.…”
Section: Arrangement and Assembly Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [68] proposed another type of acoustic metamaterial for simultaneous noise insulation and energy harvesting. The proposed structure is composed of a Helmholtz resonator and a built-in decorated membrane; the schematic diagram is shown in Figure 25.…”
Section: Established Aeh Approachesmentioning
confidence: 99%
“…Later, Chen et al continued to build an elastic-electro-mechanical model of the PMP with interface circuits (PMPICs) [20]. Zhang et al proposed an acoustic metamaterial that had dual functionality of sound insulation and energy harvesting simultaneously [21]. Existing studies have shown that PMPs provide a promising way of harvesting structural vibrations.…”
Section: Introductionmentioning
confidence: 99%